2006
DOI: 10.1021/jp0613337
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Complexation of Fisetin with Cyclodextrins

Abstract: In this work, the interaction between fisetin (3,3',4',7-tetrahydroxyflavone) (Fis) and cyclodextrins (CDs) (alpha and beta) was studied through UV-vis absorption, steady-state fluorescence, induced circular dichroism, and (1)H NMR experiments with dependence on temperature and pH. Some experimental data were compared with quantum-mechanics studies based on the SAM1 (AMPAC) semiempirical model, as well as with the B3LYP and MPW1PW91 functional models from density functional theory using the 6-311G and 3-21G ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
53
0
9

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(62 citation statements)
references
References 21 publications
0
53
0
9
Order By: Relevance
“…One study found that fisetin could only form a stable complex with β-cyclodextrin, but not with the α-cyclodextrin [11]. Complexation of fisetin with another type of cyclodextrin (γ-cyclodextrin) was also undertaken in order to understand the behaviour of fisetin in the nano-cavity, and confirmed the suitability of the nano-vehicle for parenteral administration of fisetin [12].…”
Section: Introductionmentioning
confidence: 95%
“…One study found that fisetin could only form a stable complex with β-cyclodextrin, but not with the α-cyclodextrin [11]. Complexation of fisetin with another type of cyclodextrin (γ-cyclodextrin) was also undertaken in order to understand the behaviour of fisetin in the nano-cavity, and confirmed the suitability of the nano-vehicle for parenteral administration of fisetin [12].…”
Section: Introductionmentioning
confidence: 95%
“…Hence, the ICT emission intensity should be almost unaltered because the energy barrier to form ICT state not only depends upon rotation of OH/OCH 3 but also on hydrogen bonding between the guest and the water. The energy barrier for formation of ICT state does not change as long as hydrogen bonding is still possible [33][34][35] between HCA and water molecules. So the huge enhancement of the ICT state suggests that among these two types of orientations of HCA molecule inside the CD cavity results in a huge observed enhancement of the LW band with red band shift as it is emitted from the most nonpolar state of HCA and a small enhancement of the SW state without any spectral shift.…”
Section: Emission Spectramentioning
confidence: 99%
“…So the SW band remains unaffected. When two π-moieties of the HCA are not in orthogonal position inside the CD cavity it causes an enhancement of radiative transition probability [33][34][35] of the ICT state and an increase in the ICT band. But the hydrogen bond formation of the C=O group of HCA with water molecules makes the ICT state more stable by lowering its energy level resulting in an extra red shift of the low energy (ICT) band.…”
Section: Emission Spectramentioning
confidence: 99%
“…They attributed this rate decrease to the existence of a network of hydrogen-bonded bridging waters separating the donor and acceptor in these complexes; this network would need to undergo significant rearrangement for ESPT to occur. In addition to such intermolecular proton transfer to solvent, excited-state intramolecular proton transfer (ESIPT) can also occur for specific molecules, and this process has also been extensively studied within CD cavities [91][92][93][94][95]. Once again, inclusion into a CD cavity disrupts the hydrogen bonding of the excited guest with the solvent; however, in this case, disruption of solvent hydrogen bonding actually favours intramolecular hydrogen bonding, and hence the rate of ESIPT can be enhanced upon CD inclusion [91][92][93][94].…”
Section: Cyclodextrinsmentioning
confidence: 99%
“…In addition to such intermolecular proton transfer to solvent, excited-state intramolecular proton transfer (ESIPT) can also occur for specific molecules, and this process has also been extensively studied within CD cavities [91][92][93][94][95]. Once again, inclusion into a CD cavity disrupts the hydrogen bonding of the excited guest with the solvent; however, in this case, disruption of solvent hydrogen bonding actually favours intramolecular hydrogen bonding, and hence the rate of ESIPT can be enhanced upon CD inclusion [91][92][93][94]. In other cases, direct hydrogen bonding between the guest and CD hydroxyls reduces intramolecular hydrogen bonding, resulting in a decreased rate of ESIPT [95].…”
Section: Cyclodextrinsmentioning
confidence: 99%